Chapter 11 Liminal Precarity and Compromised Agency Migrant experiences of gig work in Amsterdam, Berlin, and New York City - van Doorn, Niels (Taylor & Francis, 2023)
This chapter examines what moves migrants in the Global North to take up gig work and stick with it for various periods of time despite its by now well documented precarious conditions, by investigating the role that gig platforms play in their life-building trajectories.